2015
DOI: 10.1021/acsami.5b01901
|View full text |Cite
|
Sign up to set email alerts
|

Smart Enrichment and Facile Separation of Oil from Emulsions and Mixtures by Superhydrophobic/Superoleophilic Particles

Abstract: The separation and removal of oil or organic pollutants from water is highly imperative. The oil phases in surfactant-free oil-in-water emulsions or in free oil/water mixtures can be smartly enriched and transported by using superhydrophobic/superoleophilic iron particles (SHIPs) under a magnetic field. For water-in-oil emulsion, SHIPs-based composite membranes selectively allow the oil to pass through. Their convenient and scalable preparation, excellent separation performance, and good reusability are of gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 70 publications
(96 reference statements)
0
68
0
Order By: Relevance
“…Based on the principles mentioned above, novel materials were invented and fabricated as proof‐of‐concept. Oil–water separators are generally porous meshes, foams and sponges made from a wide range of materials, including metal, polymers, ceramics, fabrics, cellulose‐based derivatives, particles, and novel nanomaterials . Recently, Wang et al reported a highly compressible wood sponge with spring‐like lamellar structure (Figure b–d), which was fabricated by sequential chemical treatment, freeze drying and chemical vapor deposition of natural balsa wood.…”
Section: Applicationsmentioning
confidence: 99%
“…Based on the principles mentioned above, novel materials were invented and fabricated as proof‐of‐concept. Oil–water separators are generally porous meshes, foams and sponges made from a wide range of materials, including metal, polymers, ceramics, fabrics, cellulose‐based derivatives, particles, and novel nanomaterials . Recently, Wang et al reported a highly compressible wood sponge with spring‐like lamellar structure (Figure b–d), which was fabricated by sequential chemical treatment, freeze drying and chemical vapor deposition of natural balsa wood.…”
Section: Applicationsmentioning
confidence: 99%
“…The development of superhydrophobic membrane for oilwater emulsions separation was reported [112][113][114][115][127][128][129][130][131][132][133][134][135] as summarized in Table 6. However, there is no publication which clearly states the application of superhydrophobic membrane for waste lube oil processing.…”
Section: Superhydrophobic Membrane For Waste Lube Oils Processingmentioning
confidence: 99%
“…Impressive examples such as the Torrey Canyon and the Bohai Bay spill accidents, not only induced serious environment pollution, but also threatened the ecological system. [5][6][7][8][9][10][11][12][13][14] Up to now, various superhydrophobic porous materials have been prepared via various chemical and physical strategies. 4 Porous materials, including fabrics, membranes, meshes and sponges, with superhydrophobicity have believed to be promising in oil/water separation.…”
Section: Introductionmentioning
confidence: 99%